2008
DOI: 10.1002/ajmg.a.32262
|View full text |Cite
|
Sign up to set email alerts
|

The clinical spectrum of homozygous HOXA1 mutations

Abstract: We report nine new individuals from six families who have homozygous mutations of HOXA1 with either the Bosley-Salih-Alorainy Syndrome (BSAS) or the Athabascan Brainstem Dysgenesis Syndrome (ABDS). Congenital heart disease was present in four BSAS patients, two of whom had neither deafness nor horizontal gaze restriction. Two ABDS probands had relatively mild mental retardation. These individuals blur the clinical distinctions between the BSAS and ABDS HOXA1 variants and broaden the phenotype and genotype of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
89
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 16 publications
0
89
0
Order By: Relevance
“…Facial paresis and deafness were common, while swallowing dysfunction and vocal cord paresis were less often documented. 3 Our patient presented with intact vertical but restricted horizontal gaze, facial diplegia and fasciculations, and sensorineural deafness. CN VI-VIII could not be identified on MR imaging and are likely severely hypoplastic or absent.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…Facial paresis and deafness were common, while swallowing dysfunction and vocal cord paresis were less often documented. 3 Our patient presented with intact vertical but restricted horizontal gaze, facial diplegia and fasciculations, and sensorineural deafness. CN VI-VIII could not be identified on MR imaging and are likely severely hypoplastic or absent.…”
mentioning
confidence: 77%
“…The only major feature of ABDS not found in BSAS was central hypoventilation. [1][2][3] Tischfield et al and Bosley et al 2 identified homozygosity for a mutation of the HOXA1 gene in all patients with BSAS. Eight children with ABDS, including 3 new cases, were subsequently studied and were also found to have homozygous HOXA1 mutations.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations